Comparative evaluation of subcutaneous infiltration (port site) vs intraperitoneal infiltration of bupivacaine on post laparoscopic cholecystectomy pain - Gupta, R. S.; Rai, A.; Vasuniya, Vikram; Choudhary, Devendra (International Surgery Journal, 2018)
Background: Laparoscopic cholecystectomy (LC) is now the gold standard technique for the treatment of gallstones disease. Although pain after LC is less intense than after open cholecystectomy, some patients still experience considerable discomfort during early postoperative hours. The aim of this study is to evaluate the effect of intraperitoneal and port site instillation of local anaesthetics on pain relief in early postoperative period following LC. Methods: This is a randomized, prospective analytical study among patients subjected to elective laparoscopic cholecystectomy. Patients were divided into 3 groups as; Group 1 was control, Group 2 was assigned to receive portside infiltration of bupivacaine, while group 3 received combined port site and intraperitoneal instillation of bupivacaine. The evaluation of postoperative pain was done according to the visual analog scale and the dosage of narcotic analgesics consumed and duration of hospital stay was also recorded. Results: At 1st post-operative hour, minimum VAS score was in group 3 (p=0.003). At 4th post-operative hour, Minimum VAS score was in group 3(p=0.015). At 8th post-operative hour, Minimum VAS score was in group 3, (p=0.044). Patients in group 3 received a lower total amount of rescue analgesia and they also had the shortest hospital stay after LC, compared to the patients in the other groups. As regarding the incidence of right shoulder pain, group 3 has minimal no of patients experienced rt shoulder tip pain. Conclusions: Infiltration of bupivacaine into port site and intraperitoneal space is simple, inexpensive and effective technique to minimize early postoperative pain and can be practiced for elective LC.